THE DIAGNOSIS AND CLINICAL CHARACTERISTICS OF ANKYLOSING SPONDYLITIS ACCORDING TO THE DATA OF THE KAZAN CITY RHEUMATOLOGY CENTER - L I Myasoutova; S A Lapshina; A G Vasilyev; I G Salikhov (Научно-практическая ревматология)
Objective: to evaluate the specific features of the diagnosis and clinical manifestations of ankylosing spondylitis (AS) in patients followed up in the Kazan City Rheumatology Center (City Clinical Hospital Seven). Subjects and methods. Fifty-two patients who had been treated at hospital or who visited a polyclinic rheumatologist in the period February to April 2010 for a verified diagnosis of AS according to the modified New York classification criteria were examined. More than half of the patients had high clinical (BASDAI ≥4 in 71.2%) and laboratory (C-reactive protein >6 mg/l in 67.3%) activities, an active inflammatory process according to the results of magnetic resonance imaging, and a significantly limited functional state (BASFI ≥4 in 61.5%). Women were 26.9% of all the examinees, their clinical picture of peripheral arthritis prevailed, and they were referred for a rheumatologist for their being diagnosed as having reactive arthritis. Results. AS was verified an average of 4.2±1.2 years after the appearance of its first clinical symptoms, which is rather promptly as compared to the data available in the literature (on the average 7-8 years). In the peripheral form of the disease, the diagnosis was established earlier (3.7±1.4 years) than in its central form (5.1±1.8 years). These results were achieved due, among other things, to the execution of educational programs for primary physicians.